The tales of Beedle the Bard - Rowling, J. K. (New York : Children's High Level Group in association with Arthur A. Levine Books, 2008)
The Tales of Beedle the Bard, a Wizarding classic, first came to Muggle readers' attention in the book known as Harry Potter and the Deathly Hallows. Now, thanks to Hermione Granger's new translation from the ancient runes, we present this stunning edition with an introduction, notes, and illustrations by J.K. Rowling, and extensive commentary by Albus Dumbledore. Never before have Muggles been privy to these richly imaginative tales.
The wizard and the hopping pot -- The Fountain of Fair Fortune -- The warlock's hairy heart -- Babbitty Rabbitty and her cackling stump -- The tale of the three brothers.
"A wizarding classic from the world of Harry Potter"--Cover.
Accelerated Reader/Renaissance Learning
AR
Accelerated Reader
Reading Counts
Keywords: Granger, Hermione -- (Fictitious character); Dumbledore, Albus -- (Fictitious character); Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Fiction; Fantasy; Dumbledore, Albus -- (Fictitious character); Granger, Hermione -- (Fictitious character); Hogwarts School of Witchcraft and Wizardry (Imaginary organization); Magic; Wizards; Fairy tales; Fantasy fiction; Short stories; Fantasy fiction, English; Fantasy fiction; Fairy tales; Fantasy; Short stories; Fantasy fiction; Fantasy fiction, English; Fiction; Juvenile works; Fantasy fiction; Fantasy fiction; 1290L.